1964
DOI: 10.2466/pms.1964.19.2.619
|View full text |Cite
|
Sign up to set email alerts
|

Structural Advantage of the Mechanism of Spoken Expression as a Factor in Differences in Spoken and Written Expression

Abstract: Spoken expression produces significantly more cognitive and linguistic material than written expression. This experiment tested whether the facility of the organ of use was, in part, responsible by examining different, and more facile writing techniques (writing, typing, stenotyping) on the same variables. As facility increases in the writing mode, cognitive and linguistic indices do approach those previously found in spoken expression, but still differ significantly from them. Speaking, although an overlaid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…For purposes of comparison, were we to use the articulation and speech rates (5.17 and 3.43 syllables/sec, respectively) from the archival data for storytelling (Kowal et al, 1983), speakers would be found to articulate six times as fast as writers and to produce almost seven times as fast. This factor of seven corresponds closely to that of both Blass and Siegman (1975) and Horowitz and Berkowitz (1964).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For purposes of comparison, were we to use the articulation and speech rates (5.17 and 3.43 syllables/sec, respectively) from the archival data for storytelling (Kowal et al, 1983), speakers would be found to articulate six times as fast as writers and to produce almost seven times as fast. This factor of seven corresponds closely to that of both Blass and Siegman (1975) and Horowitz and Berkowitz (1964).…”
Section: Discussionmentioning
confidence: 89%
“…However, this rationale is basically associated with different social settings for speaking and for writing. Accordingly, Blass and Siegman (1975) found speech and writing rates of 3.03 and 0.43 words/sec, respectively (a factor of7.0, compared to that of7.2 in Horowitz & Berkowitz, 1964); however, writing yielded a lower percentage of offtime/total time than did speaking. Gould and Quinones (1978) described a videotape methodology for recording the temporal course of writing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Horowitz & Berkowitz, 1964). That study argued that the language in messages that were steno-typed showed more features that are normally associated with the spoken register, than messages that were hand-written or typed on a typewriter.…”
Section: Features Of Cmc and In£uencing Factorsmentioning
confidence: 99%
“…Du Bartell, 1995, among others). Instant messaging, such as communicated via WebWho, is spontaneous and fast, and has a number of features in common with the spoken register; it is playful, dynamic and speech-like (Horowitz & Berkowitz, 1964;cf. Bolter, 1991).…”
Section: Comparison With Speech and Traditionally Written Language Amentioning
confidence: 99%